Correlating RANK Ligand/RANK Binding Kinetics With Osteoclast Formation and Function. Issue 11 (9th September 2015) - Warren, Julia T.; Zou, Wei; Decker, Corinne E.; Rohatgi, Nidhi; Nelson, Christopher A.; Fremont, Daved H.; Teitelbaum, Steven L.
ABSTRACT The interaction between Receptor Activator of NF‐κB Ligand (RANKL) and its receptor RANK is essential for the differentiation and bone resorbing capacity of the osteoclast. Osteoprotegerin (OPG), a soluble homodimer, acts as a decoy receptor for RANKL and thus inhibits osteoclastogenesis. An imbalance in the RANKL/RANK/OPG axis, with decreased OPG and/or increased RANKL, is associated with diseases that favor bone loss, including osteoporosis. Recently, we established a yeast surface display system and screened libraries of randomly mutated RANKL proteins to identify mutations that abolish binding to OPG while preserving recognition of RANK. These efforts yielded several RANKL variants possessing substantially higher affinity for RANK compared to their wild‐type (WT) counterpart. Using recombinant RANKL mutant proteins, we find those with increased affinity for RANK produce more robust signaling in osteoclast lineage cells and have greater osteoclastogenic potential. Our results are the first to document gain of function RANKL mutations. They indicate that the physiological RANKL/RANK interaction is not optimized for maximal signaling and function, perhaps reflecting the need to maintain receptor specificity within the tumor necrosis factor superfamily (TNFSF). Instead, we find, a biphasic relationship exists between RANKL/RANK affinity and osteoclastogenic capacity. In our panel of RANKL variants, this relationship is driven entirely by manipulation of the kinetic off‐rate. Our structure‐based and yeast surface display‐derived insights into manipulating this critical signaling axis may aid in the design of novel anti‐resorptive therapies as well as provide a paradigm for design of other receptor‐specific TNF superfamily ligand variants. J. Cell. Biochem. 116: 2476–2483, 2015. © 2015 Wiley Periodicals, Inc.